Central Bank Digital Currencies and It’s Potential Impact on the Profitability and Systems Stability of Commercial Banking in Emerging Markets - Jailani, Novalini; Anwar, Khairul; Maulida, Minati; Muhammad, Adib (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
The development of Central Bank Digital Currencies (CBDCs) has become a significant topic of discussion globally, particularly in emerging markets where financial inclusion, monetary sovereignty, and banking stability are key concerns. This study explores the potential impact of CBDC implementation on the profitability and system stability of commercial banking systems in these economies. This research adopts a qualitative approach through a literature review of CBDC implementations in key emerging economies, including China, Nigeria, Brazil, Russia, and India. The study finds that while CBDCs can enhance efficiency and financial accessibility, their impact varies depending on a country's banking infrastructure, regulatory framework, and financial stability measures. In some cases, CBDCs have exacerbated liquidity risks for commercial banks, while in others, they have promoted digital innovation and alternative revenue streams. The findings highlight the need for strategic collaboration between central banks and commercial financial institutions to mitigate risks while leveraging the benefits of CBDCs. Policy recommendations include implementing limits on CBDC holdings, integrating CBDCs with existing banking services, and fostering regulatory frameworks that support a balanced financial ecosystem. This study contributes to the academic discourse on digital currencies and banking by offering insights into the evolving role of central banks and commercial banks in the digital financial landscape.